Packable hyperbolic surfaces with symmetries. Issue 1 (11th March 2023) - Dostert, Maria; Kolpakov, Alexander
Abstract: We discuss several ways of packing a hyperbolic surface with circles (of either varying radii or all being congruent) or horocycles, and note down some observations related to their symmetries (or the absence thereof).